Navigating Research Formatting Dilemmas among College Students: Extent of Formal Instruction and Access to Resources Toward Ramified Research Guidelines - Pecson, Ryan; Quintos Jr, Romeo; Olubia, Leandro; Santos, Lourdes; Forbes, Jaime; Lugtu, Normita; Santos, Paulo Joseph (Indonesian Journal of Teaching and Learning, 2025)
Purpose – This study aims to determine the extent of formal instruction or guidance on research formatting among college students, as well as the availability of resources to assist them in addressing research formatting issues in a state university in the Philippines. The research intends to inform the development of standardized and effective research guidelines for higher education institutions. Methodology – The study employed a descriptive qualitative design using semi-structured interviews. Fifteen (15) purposively selected student research leaders participated in the interview process. Stringent research protocols and ethical considerations were strictly followed. Data from the interview transcripts were analyzed using Clarke and Braun’s thematic analysis approach to identify recurring patterns and insights. Findings – The results reveal that the degree of formal instruction on research formatting significantly influences students’ ability to manage and complete their research projects, impacting both efficiency and quality. Identified challenges include limited guidance, inconsistent formatting standards, and resource constraints. Key strategies to overcome these challenges include faculty mentoring, accessible support systems, and standardized institutional policies. Novelty – This study provides an in-depth exploration of research formatting challenges from the perspective of student research leaders—an often underrepresented group in academic discourse—highlighting the interplay between formal instruction, resource access, and research productivity. Significance – The findings serve as a valuable reference for higher education administrators, faculty, and policymakers in crafting research guidelines that enhance students’ efficiency, reduce anxiety, and foster innovation in research practices.